Foreign Direct Investment and Trade Creation - Pontes, José Pedro (2010)
This paper presents a theory of a nonmonotonic relationship between foreign direct investment (henceforth FDI) and trade that fits with the results of empirical studies. It departs from the traditional theories of international investment (both vertical and horizontal) that postulated simple patterns of relationship between FDI and trade with regard to trade costs. It is assumed that two vertically-related firms decide simultaneously to have a single plant in a home country or to have also a second plant in a foreign country. FDI and trade behave as substitutes for high values of market size (with relation to fixed costs) and either as substitutes or complements for low values of market size, the balance depending on trade costs. The possible complementarity between FDI and trade follows from the fact that too high trade costs on intermediate goods prevent FDI from taking place.